VISCOSITY TEST OF VEHICLE ENGINE OILS - Prasetyowati, Rita (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
This study aims to determine the value of the kinematic viscosity lubricants motorcycle that has been used at various temperatures and the use of distance. This study also aims to remedy mengtahui how the value of the kinematic viscosity of the lubricant car that has been used in a wide range of temperature variation and distance usage. Viscosity liquid, in this case is the lubricants, can be determined using the Redwood viscometer By using Redwood viscometer, can be measured flow time required by 50 ml of the sample at a constant temperature. Time measurement result is known as the Redwood's sec or conventional viscosity. Conventional viscosity can be determined from the kinematic viscosity values. For motorcycle lubricant viscosity measured at a temperature of 30ͦ C, 50ͦ C, 65ͦ C and 100ͦ C, with the use of distance variation 0 Km, 5 Km, 10 Km, 15 Km and 20 Km. For car lubricant viscosity measured at a temperature of 30ͦ C, 50ͦ C, 65ͦ C and 100ͦ C, with variations in the use of distance 0 km, 1000 km, 5000 km, and 10000 Km. Motorcycle lubricant viscosity values at a temperature of 100ͦ C is 9.54 m2 / s (new lubricant), 1.15 m2 / s (use 5 Km), 5.86 m2 / s (use of 10 Km), 8.02 m2 / s (use of 15 Km), and 9.11 m2 / s (use of 20 Km). Lubricant viscosity values at a temperature of 1000C car is 6.73 m 2 / s (new lubricant), 7.89 m2 / s (use 1,000 km), 6.0 m2 / s (use 5000 Km), and 7.55 m2 / s (use 10000 Km). Keywords: viscosity, oil, temperature